KERJASAMA TIM LINTAS FUNGSI DAN KINERJA MANAJEMEN PROYEK - Aldi, Benediktus Elnath; Utomo, Hargo (Journal of Indonesian Economy and Business, 2003)
This paper examines the linkage between cross-functional teamwork and project management performance. The main thrust of the study is continuing debates on how cross-functional teamwork contributes to project management performance: on-time, on-budget, and on-purpose. The level of influence was observed based on six critical factors: the clarity of super-ordinate goals, conformity of project team members to organization rules and procedures, physical proximity of each project team members, accessibility of project team members, knowledge sharing amongst project team members, and fairness of selection process of the project team members.The study uses combination of survey and case studies approach to answer such complex question. Samples were driven from 44 healthcare projects under the coordination of Health Department in East Java involving 88 respondents in the study. The hierarchical regression analysis was then used to explain major antecedents of cross-functional teamwork on the performance of project management.The study concludes that successful project management accounts multi-dimensional issues. The clarity of super-ordinate goals and physical proximity of team members have positive and significant influence in the performance of cross-functional teamwork. These invite further research to improve generalizability of the study.Keywords: project management, performance, cross-functional teamwork.